2013
DOI: 10.1080/09712119.2013.782869
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of growth performance, meat quality and haematological parameters of three-way crossbred chickens with reciprocal F1 crossbred chickens in a subtropical environment

Abstract: Ahmed (2013) Comparative study of growth performance, meat quality and haematological parameters of three-way crossbred chickens with reciprocal F1 crossbred chickens in a subtropical environment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
3
10
2
Order By: Relevance
“…The average 20-week BW of CHE and FAH were resembling with Nigerian native chicken (Sola-Ojo et al, 2011). Similarly, crossbred CF chickens' weight was consistent with the study of Khawaja et al (2013), who reported that the BW of 2-way and 3-way crossbred chickens were 1236.50 and 1288.73 g, respectively. However, some various weights of 20-week of age were published (Mosaad et al, 2010;Osei-Amponsah et al, 2012;Khadda et al, 2017;Sarma et al, 2018).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The average 20-week BW of CHE and FAH were resembling with Nigerian native chicken (Sola-Ojo et al, 2011). Similarly, crossbred CF chickens' weight was consistent with the study of Khawaja et al (2013), who reported that the BW of 2-way and 3-way crossbred chickens were 1236.50 and 1288.73 g, respectively. However, some various weights of 20-week of age were published (Mosaad et al, 2010;Osei-Amponsah et al, 2012;Khadda et al, 2017;Sarma et al, 2018).…”
Section: Resultssupporting
confidence: 88%
“…Considering the average daily feed intake, the range of 48.72 to 50.76 was found in our chickens (data not shown). FI values in this study were lower than some previous publications (Kittichonthawat et al, 2003;Suayroop et al, 2012;Khawaja et al, 2013). Several authors reported that the various results of feed intake were a response of the breed differences (Van Marle-Köster and Casey, 2001;Castellini et al, 2002;Azharul et al, 2005;Castellini et al, 2016).…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Chickens (males as a-c Means in a row with no common superscript differ significantly at P ≤ 0.05. 1 Values are least square mean ± standard error. RNN = Rhode Island Red × Naked Neck; BNN = Black Australorp × Naked Neck; NN = Naked Neck; FR = free-range; SI = semiintensive; I = intensive; WAS = weight at slaughter (g); DW = dressed weight (g); CY = carcass yield (%); LW = liver weight (g); HW = heart weight (g); GW = gizzard weight (g); BW = breast weight (g); IW = intestinal weight (g); IL = intestinal length (cm); NW = neck weight (g); WW = wings weight (g); DMW = drumstick weight (g); TW = thigh weight (g); R&BW = ribs and back weight (g).…”
Section: Traitmentioning
confidence: 99%
“…In Pakistan, Lyallpur Silver Black breed was evolved by crossing Desi with three imported breeds; namely White Leghorn, White Cornish and New Hampshire in a four-line crossbreeding programme (Ashraf et al 2003). Chickens from White Leghorn male crossbred with F1 female (Fayoumi males crossed with Rhode Island Red females) gained better body weight and lower mortality and three-way crossbred chickens of Rural Leghorn showed better FCR and lower mortality than two-way reciprocal crossbred chickens of Fayoumi males crossed with Rhode Island Red females (Khawaja et al 2013).…”
Section: Introductionmentioning
confidence: 99%